Cervantes, Menard in Borges - Chartier, Roger (Primerjalna književnost, 2011)
The article examines Borges's "Pierre Menard, Author of the Quixote" from the biographical, autobiographical, allegorical, critical, aesthetic and bibliographical perspective. In all these contexts, the story reveals itself as either explicitly or implicitly self-referential, reading in each instance itself in its relation to the author, the publication and the reader.
Keywords: Borges, Jorge Luis, 1899-1986; "Pierre Menard, autor del Quijote"; Literarne študije; Cervantes Saavedra, Miguel de, 1547-1616; literarni liki; fiction; fikcija; pastiš